Should HAS-BLED scoring be revised for better risk estimation in patients with intracerebral hemorrhage?. (August 2014) - Ince, Birsen; Benbir, Gulcin; Gozubatik-Celik, Gokcen
<x xml:space="preserve">Abstract</x> Many efforts have been made to develop decision-support tools and bleeding prediction schemes to start or resume anticoagulation after intracerebral hemorrhage, related with anticoagulation use or not, such as CHA2DS2-VASc or HAS-BLED scoring. HAS-BLED is a validated scoring system to predict the risk of major bleeding in a patient with atrial fibrillation; some current scientific guidelines suggest its use in 'risk–benefit' reasoning when deciding whether to start long-term oral anticoagulation. Here the authors present a patient with atrial fibrillation and intracerebral hemorrhage, and aim to discuss the use of HAS-BLED, suggesting that some revisions may help better management of these patients for major bleeding risk.